Physiology and Pathophysiology of Iron Metabolism - Enko, Dietmar (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focuses on the importance of the micronutrient iron in human physiological iron homeostasis and iron-related diseases. Daily adequate dietary iron supply ensures vital body functions and hemoglobin synthesis during erythropoiesis. During the last few decades, scientific evidence has shown that the maintenance of human iron homeostasis is an important factor for physical and mental health. The present reprint gives an overview of how iron, as an essential dietary element, is responsible for physiological and pathological biochemical processes in the human body. For the readership, this relevant information will provide an evidence-based update on the complex regulatory mechanisms and related diseases of iron metabolism.